Characteristics associated with significantly worse quality of life in mycosis fungoides/Sézary syndrome from the Prospective Cutaneous Lymphoma International Prognostic Index (PROCLIPI) study. (28th July 2019) - Molloy, K.; Jonak, C.; Woei‐A‐Jin, F.J.S.H.; Guenova, E.; Busschots, A.M.; Bervoets, A.; Hauben, E.; Knobler, R.; Porkert, S.; Fassnacht, C.; Cowan, R.; Papadavid, E.; et al.
Summary: Background: Mycosis fungoides (MF) and Sézary Syndrome (SS) are the most common cutaneous T‐cell lymphomas. MF/SS is accompanied by considerable morbidity from pain, itching and disfigurement. Aim: To identify factors associated with poorer health‐related quality of life (HRQoL) in patients newly diagnosed with MF/SS. Methods: Patients enrolled into Prospective Cutaneous Lymphoma International Prognostic Index (PROCLIPI; an international observational study in MF/SS) had their HRQoL assessed using the Skindex‐29 questionnaire. Skindex‐29 scores were analysed in relation to patient‐ and disease‐specific characteristics. Results: The study population consisted of 237 patients [60·3% male; median age 60 years, (interquartile range 49–70)], of whom 179 had early MF and 58 had advanced MF/SS. In univariate analysis, HRQoL, as measured by Skindex‐29, was worse in women, SS, late‐stage MF, those with elevated lactate dehydrogenase, alopecia, high modified Severity Weighted Assessment Tool and confluent erythema. Linear regression models only identified female gender (β = 8·61; P = 0·003) and alopecia (β = 9·71, P = 0·02) as independent predictors of worse global HRQoL. Item‐level analysis showed that the severe impairment in symptoms [odds ratio (OR) 2·14, 95% confidence interval (CI) 1·19–3·89] and emotions (OR 1·88, 95% CI 1·09–3·27) subscale scores seen in women was caused by more burning/stinging, pruritus, irritation and greater feelings of depression, shame, embarrassment and annoyance with their diagnosis of MF/SS. Conclusions: HRQoL is significantly more impaired in newly diagnosed women with MF/SS and in those with alopecia. As Skindex‐29 does not include existential questions on cancer, which may cause additional worry and distress, a comprehensive validated cutaneous T‐cell lymphoma‐specific questionnaire is urgently needed to more accurately assess disease‐specific HRQoL in these patients. What's already known about this topic? Cross‐sectional studies of mixed populations of known and newly diagnosed patients with mycosis fungoides (MF)/Sézary syndrome (SS) have shown significant impairment in health‐related quality of life (HRQoL). Previous studies on assessing gender‐specific differences in HRQoL in MF/SS are conflicting. More advanced‐stage disease and pruritus is associated with poorer HRQoL in patients with MF/SS. What does this study add? This is the first prospective study to investigate HRQoL in a homogenous group of newly diagnosed patients with MF/SS. In patients newly diagnosed with MF/SS, HRQoL is worse in women and in those with alopecia and confluent erythema. MF/SS diagnosis has a multidimensional impact on patient HRQoL, including a large burden of cutaneous symptoms, as well as a negative impact on emotional well‐being. Abstract : Linked Comment: Talpur. Br J Dermatol 2020; 182 :541–542 . Plain language summary available online